Establishment of X chromosome inactivation and epigenomic features of the inactive X depend on cellular contexts. (8th July 2016) - Vallot, Céline; Ouimette, Jean‐François; Rougeulle, Claire
Abstract : X chromosome inactivation (XCI) is an essential epigenetic process that ensures X‐linked gene dosage equilibrium between sexes in mammals. XCI is dynamically regulated during development in a manner that is intimately linked to differentiation. Numerous studies, which we review here, have explored the dynamics of X inactivation and reactivation in the context of development, differentiation and diseases, and the phenotypic and molecular link between the inactive status, and the cellular context. Here, we also assess whether XCI is a uniform mechanism in mammals by analyzing epigenetic signatures of the inactive X (Xi) in different species and cellular contexts. It appears that the timing of XCI and the epigenetic signature of the inactive X greatly vary between species. Surprisingly, even within a given species, various Xi configurations are found across cellular states. We discuss possible mechanisms underlying these variations, and how they might influence the fate of the Xi. Abstract : X chromosome inactivation initiates during early mammalian development in a manner that correlates with cellular differentiation, and the mechanisms coupling these processes are starting to be unraveled. Once established, the inactive status is stably transmitted throughout cell divisions. Recent data highlight, however, variation in Xi features, both within and across species.